2003
DOI: 10.1007/s00432-003-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of biomolecular profiles in primary high-grade prostate cancer treated by radical prostatectomy

Abstract: According to our data, tumour grade is clearly associated with a change in the biomolecular profile, even between patients with similar serum PSA levels. As the prognosis of HG prostate cancer is poor, these tumours should be analysed by immunohistochemical staining to identify specific tumour features for an appropriate selection of adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
5
12
0
1
Order By: Relevance
“…Additionally, we evaluated a potential mechanism of Bcl‐2 overexpression on protein level. Against the background of negative regulation of p53 and Bcl‐2 expression 1 we tried to link both biomarker, but no such correlation was present what confirms findings from large sections 15–17.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, we evaluated a potential mechanism of Bcl‐2 overexpression on protein level. Against the background of negative regulation of p53 and Bcl‐2 expression 1 we tried to link both biomarker, but no such correlation was present what confirms findings from large sections 15–17.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, there seems to be a clear stratification between predominantly Gleason 3 pattern tumours and those containing Gleason 4 morphology [16]. This change in morphology in the Gleason 4 pattern is undoubtedly a visual clue towards the myriad of genetic and protein changes which allow these cells to have greater metastatic potential, as shown by recent studies revealing immunohistochemical and gene array changes [17,18]. Second, these studies provide indirect evidence that the Gleason grading system is reproducible across different institutions, as the correlations between GS and outcome variables are very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them suggest that immunohistochemical p53 positivity increases with high grade, advanced stage and peripheral zone origin. [3][4][5][6][7] Some studies have suggested that nuclear p53 accumulation may correlate with poor prognosis after radical prostatectomy, 8,9 external beam radiation, 10 and watchful waiting 11 but these data were not confirmed in other studies. [12][13][14] Perhaps some of these discordances were caused by the relatively small number of patients included in these studies ranging from 24-392 patients.…”
mentioning
confidence: 95%